Mitigating rice production risks from drought through improving irrigation infrastructure and management in China1. (5th December 2017) - Wang, Yangjie; Huang, Jikun; Wang, Jinxia; Findlay, Christopher
Abstract : Rice, China's most important food crop, is highly dependent on irrigation, but an increasing number of extreme drought events have challenged rice production in many regions. This paper investigates the role of local irrigation infrastructure in improving farmers' ability to respond to drought and its effectiveness in mitigating the drought risk in rice production in China. The analysis relies on a moment‐based specification of the stochastic production function, capturing mean, variance and skewness effects. Using household survey data from 86 villages in five provinces, we jointly estimate farmers' adaptive irrigation decisions and their effects on rice yield and production risk. Our econometric analyses show that irrigation infrastructure in villages contributes to enhancing farmers' irrigation capacity in adapting to drought, and increased irrigation leads to a significant increase in mean yield and a reduction in exposure to risk as well as downside risk in rice production. The paper concludes with policy implications.